Effects of Transfer Pricing, Tax Haven, and Thin Capitalization on Tax Avoidance - I Gusti Ayu Intan Saputra Rini; Mellisa Dipa; Cokorda Krisna Yudha (Universitas Warmadewa, 2022)
Tax avoidance can be defined as an effort made by taxpayers to ease their tax burden without violating tax rules. Tax avoidance is a complicated and distinctive problem because it does not violate existing rules and regulations, however, on the other hand, the government does not want the existence of tax avoidance because it can cause a lack of state revenue. The purpose of this study is to examine and obtain empirical evidence of the effect of transfer pricing, tax havens, and thin capitalization on tax avoidance. This study was conducted on basic and chemical industrial sector companies listed on the Indonesia Stock Exchange for the 2017-2020 period. The sample was determined using a non-probability sampling method through a purposive sampling technique, and 13 samples of companies that meeting the criteria were obtained. In addition, this study uses secondary data in the form of company annual financial statements and reports. Data were analysed using a multiple linear regression analysis technique. The results showed that transfer pricing has a negative effect on ETR as a proxy for tax avoidance; tax haven has a positive effect on ETR; while thin capitalization has no effect on ETR.